A dynamic virtual try-on simulation framework for speed skating suits - Xiao, B.; Hu, Z.; Liu, Z.; Liu, L. (The Journal of the Textile Institute, 2023)
Speed skating suits have important effects on performance of athletes, and they also protect human body to avoid injury in competitions. Appropriate patterns including structure and shape influence the wearing comfort, which is a main factor of athletes` action performance. Sport wears provide different pressure on human body because of their surface tension, and suitable pressure is helpful to athletes to perform actions freely. However, design and adjustment of tight-fitting suits to achieve satisfying press distribution are hard works, because the pressure distribution cannot be measured directly in dynamic process of sport actions. This paper proposes a dynamic virtual try-on simulation framework for speed skating suit. First, a skeleton supported virtual human model with fixed structure skin mesh is created, and the model can be deformed according to speed skating actions. Second, a typical sport suit including 5 parts is created on the human body skin model as a virtual try-on framework, thus all the suit`s parts are deformed driven by human model. Finally, deformations of suit parts are calculated frame-by-frame in dynamic process, and the deformation rate is considered as the tense distribution of fabric which can be transformed to pressure by curvature radius. The deformation rate distribution of different area on three-dimensional suit part provides a direct visual reference to the pattern adjustment. The results show that our framework is feasible to speed skating suit pattern making works.